ответ: 2. -1.
Объяснение:
Розв'язати систему рівнянь підстановки
2x+y=3; (1)
-3x+4y=-10. (2)
Из (1)
у=3-2х подставляем в (2):
-3x+4(3-2x)=-10;
-3x+12-8x=-10;
-3x-8x=-10-12;
-11x=-22;
x=2 подставляем в (1):
2*2+у=3;
y=3-4;
y=-1.
{2х+у=3
{-3х+4у=-10
{у=3-2х
-3х+4(3-2х)=-10
-3х+12-8х=-10
-11х+12=-10
-11х=-22
х=-22÷(-11)
х=2
у=3-2*2
у=-1
ответ : ( 2 ; -1 ).
ответ: 2. -1.
Объяснение:
Розв'язати систему рівнянь підстановки
2x+y=3; (1)
-3x+4y=-10. (2)
Из (1)
у=3-2х подставляем в (2):
-3x+4(3-2x)=-10;
-3x+12-8x=-10;
-3x-8x=-10-12;
-11x=-22;
x=2 подставляем в (1):
2*2+у=3;
y=3-4;
y=-1.
{2х+у=3
{-3х+4у=-10
{у=3-2х
{-3х+4у=-10
-3х+4(3-2х)=-10
-3х+12-8х=-10
-11х+12=-10
-11х=-22
х=-22÷(-11)
х=2
у=3-2*2
у=-1
ответ : ( 2 ; -1 ).